ANALYSIS OF THE EFFECT OF NON-PERFORMING FINANCING (NPF) AND OPERATING EXPENSES TO OPERATING INCOME (BOPO) RATIO ON RETURN ON ASSETS (ROA) IN INDONESIAN ISLAMIC COMMERCIAL BANKS 2020-2024 - Sabila Farodisa; Nuntupa; Yeni Kartikawati (Majapahit Journal of Islamic Finance and Management, 2026)
The financial performance of Islamic commercial banks is one of the important indicators used to assess the health level and profitability level of the bank, one of which can be measured through Return on Assets (ROA). Factors that are suspected to affect ROA include Non-Performing Financing (NPF) and Operating Expense to Operating Income (BOPO) Ratio. This study aims to analyze the influence of NPF and BOPO on ROA in Islamic commercial banks in Indonesia for the 2020-2024 period. Using a quantitative approach as well as secondary data obtained from the company's financial statements. The data analysis technique used multiple linear regression with the help of SPSS software version 26. The results of this study show that NPF partially has no effect on ROA with a significance value of 0.202 > 0.05, while BOPO has a significant effect on ROA as evidenced by a significance value of 0.001 < 0.05. Meanwhile, simultaneously a score of 0.001 < 0.05 was obtained, which means that NPF and BOPO have a significant effect on ROA.